The conditions of Hyers—Ulam—Rassias-stability of a set of equations - Martynyuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2017)
For a set of regularized equations and a set of equations with causal operators, the sufficient conditions of Hyers—Ulam—Rassias-stability are obtained.